PENERAPAN METODE PEMODELAN DALAM MENINGKATKAN KEMAMPUAN BERPIDATO DI KELAS VI MADRASAH IBTIDAIYAH ALKHAIRAAT KOTARINDAU - Yuliyanty, Yuliyanty; Karim, Ali; Tahir, Moh. (BAHASANTODEA, 2017)
This study aims to improve the ability to make speeches of grade 6 students Madrasah Ibtidaiyah Alkhairaat Kotarindau. This study is a classroom action research consisting of two cycles, each cycle is held twice in class and each cycle consists of four stages, namely planning, implementation, observation, and reflection. Collecting techniques in this study are the provision of preliminary tests and final tests of action, observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. Individual mastery indicator 65% and classical completeness 80%. The assessment component of speech, ie, pronunciation, intonation and expression in speech. The result of the cycle I average completeness of individuals reached 61.29 %% and classical completeness reached 65.05%. The results of the assessment cycle II has a significant increase of the average completeness of individuals reached 80.64% and classical completeness reached 90.32%. Thus it can be concluded that learning by using modeling method can improve students' ability to give speech in grade VI Madrasah Ibtidaiyah Alkhairaat Kotarindau.